Knee and hip loading patterns at different phases in the menstrual cycle: Implications for the gender difference in anterior cruciate ligament injury rates - Chaudhari, A. M. W.; Lindenfeld, T. N.; Andriacchi, T. P.; Hewett, T. E.; Riccobene, J.; Myer, G. D.; Noyes, F. R. (The American Journal of Sports Medicine, 2007)
Background: Menstrual cycle phase has been correlated with risk of noncontact anterior cruciate ligament injury in women. The mechanism by which hormonal cycling may affect injury rate is unknown.